Landsat 8 Observation of the Internal Solitary Waves in the Lombok Strait - I Wayan Gede Astawa Karang; Chonnaniyah Chonnaniyah; Takahiro Osawa (Indonesian Journal of Geography, 2019)
Landsat  8,  Landsat  Data  Continuity  Mission  (LDCM)  satellite,  was  launched  on  11 February 2013 with Operation Land Imager (OLI) sensors. Tis sensor has better radiometric performance than the previous mission, which is quantized in the 12-bit dynamic range due to an increase in the signal-to-noise (SNR) ratio. In this analysis, the spatio-temporal distribution of the propagation of the internal solitary wave (ISW) in the Lombok Strait was extracted from the Landsat 8 images described for the ﬁrst time.  Tere were 14 ISW events studied for period 2014  -  2015  using  Landsat  8.  Te  manifestations  of  ISW  recorded  on  Landsat  8  images  were then extracted using digitization method to investigate and measure several parameters and ISW distribution in the Lombok Strait. Te estimation results of the average ISW phase velocity in this study are 2.05 ms-1 with the direction of propagation heading north at an average angle of 19.08°. Tis study has shown that Landsat 8 can be used to monitor and analyze several internal wave parameters in the ocean.